Effectiveness of the Maguerez Arch in nursing teaching on vesical catheterism: an almost experimental study - Jonatan Deyson do Nascimento de Sousa; Cristina da Silva Fernandes; Maria Aline Moreira Ximenes; Joselany Áfio Caetano; Nelson Miguel Galindo Neto; Lívia Moreira Barros (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To evaluate the effectiveness of the Arco de Maguerez in teaching nursing students about the Bladder Catheter. Method Quasi-experimental study conducted at a public university in northeastern Brazil, with 29 students, in a single group, in the period of october 2018. Data were collected before and after using the Arco de Maguerez in educational intervention, using validated instruments, referring to knowledge and practice. IBM SPSS Statistics software version 24 was used for statistical analysis. The level of significance was set at 5% and the 95% confidence interval. Data analysis was performed using the McNemar and Mann-Whitney test. Results The median of correct answers for knowledge was 7, in the pre-test, and 9 in the post-test (p> 0.001). Regarding practice, in the pre-test the median of correct answers was 28 and, in the post-test, it went to 36, p> 0.001. The academics explained that the AM technology based on the problematization of a fictitious clinical case made learning about Bladder Catheterization Delay clear and feasible. Conclusion The Arco de Maguerez was effective in improving the knowledge and skill of nursing students regarding the Bladder Catheter.